Myeloid-derived growth factor regulates high glucose-mediated apoptosis of gingival fibroblasts and induce AKT pathway activation and nuclear factor κB pathway inhibition - Linlin Gao; Zhenqiang Li; Wenxiao Chang; Yanyan Liu; Nan Zhang (Elsevier, 2023)
Background: /purpose: Periodontal disease is a chronic inflammatory disease that occurs in the tissues that support and attach teeth. There is considerable evidence of a relationship between diabetes and periodontal disease. Emerging studies have reported that myeloid-derived growth factor (MYDGF) can inhibit apoptosis and inflammation. The purpose of this study was to investigate whether MYDGF mediates the role of hyperglycemia in fibroblasts in periodontitis tissues. Materials and methods: Fibroblasts were isolated and cultured from normal gums. Gene expression levels were detected by RT-PCR. The protein level was detected by western blotting. Cell viability was determined by MTT assay. To investigate the role of MYDGF, the plasmid was transfected into fibroblasts. The expression levels of cytokines were determined by ELISA. Results: High glucose can down-regulate the expression of MYDGF in human gingival fibroblasts in a time-dependent manner, and decrease the fibroblast activity. SOD level was decreased and MDA level was increased in gingival fibroblasts by high glucose. High glucose up-regulates pro-apoptotic indicator Bax, down-regulates anti-apototic indicator Bcl-2, and increased endoplasmic reticulum stress related indicators Nox 2, GRP78, ATF6, and PERK. In addition, high glucose increased TNF-α, IL-1β, IL-8 and CXCL1 protein levels in fibroblasts. Our study also found that high glucose inhibits the AKT signaling pathway and activates the nuclear factor κB (NF-κB) pathway. Interestingly, overexpression of MYDGF reversed these effects. Conclusion: MYDGF is down-regulated in gingival fibroblasts induced by high glucose. Overexpression of MYDGF inhibits apoptosis induced by high glucose, inhibits oxidative stress and cytokine secretion of gingival fibroblasts induced by high glucose, and induces AKT pathway activation and NF-κB pathway inhibition.